“MEDICIÓN Y EVALUACIÓN DE LA CALIDAD DEL SERVICIO, A TRAVÉS DEL MODELO SERVQUAL EN LA COOPERATIVA DE AHORRO Y CRÉDITO “CREDIAMIGO” LOJA LTDA, AÑO 2018 - HURTADO TREJO, STEFANY LIZBETH (2019)
With the purpose of contributing to the social welfare of the partners and clients of the Cooperative "Crediamigo" and to the economic development of the same, the present investigation was carried out whose general objective was to Measure and evaluate the quality of the service, through the model ServQual in the Savings and Credit Cooperative "Crediamigo" Loja Ltda. Year 2018. For this, a descriptive-applied research was carried out with a quantitative and qualitative approach using the inductive, deductive, analytical and synthetic methods; The study population was 8005 people, where a sample of 366 partners and clients was obtained, in addition the ServQual model was used, which allows us to measure, evaluate and improve the quality of service offered by an institution, through two type surveys that reveal the perceptions and expectations of the partners and clients of the entity; The questionnaires type 22 questions distributed according to the five dimensions accepted by the model which are: tangible elements, which refers to the infrastructure, physical appearance and equipment of the institution; reliability, which means the ability to perform the service in a careful and reliable way; responsiveness, is the willingness and willingness to help users and provide a fast service; Reliability refers to the knowledge shown by employees and their abilities to arouse credibility and confidence; empathy describes the personalized attention that the organization offers its clients. From the results of the surveys to measure the satisfaction applied to the 366 partners and clients of the financial institution, it was determined that Cooperative "Crediamigo" Ltda. Obtained an Excellent rating with 93/100 percent with respect to the offered service. n effect of the evaluation of the Service Quality Index -ICS- had a negative value of 0.07 (-7%) which means that there is a small dissatisfaction gap in the service received by the cooperative's officials, it should be emphasized that in spite of presenting a low result, any value different from zero in negative is recognized as service dissatisfaction, that is to say, that the perceptions do not exceed or even the expectations. It is important to allude that the surveys of perception and expectation applied allow to measure the satisfaction of the users, and the -ICS- instead reflects the dissatisfaction of the same ones.